The Effect of Corporate Social Responsibiity on Financial Performance. A Case Study of Centenary Bank, Kabale Branch - Victor Ainembabazi (Uganda Christian University, 2026)
This study looks into how Corporate Social Responsibility (CSR) projects are impacting the financial performance of Kabale Branch Centenary Bank Uganda. Although the correlation between CSR and enhanced corporate performance is increasingly prevalent at the international level, specific evidence at the branch level for specific regions notably, for developing countries including Uganda is scarce. The following analysis is a mixture of methods, focus on 2020 to 2025. It integrates quantitative survey responses from all the stakeholders, in-depth report-writing comments and financial statements of the respective banks into a systematic and process-based analysis tailored to specific contexts. The findings demonstrate explicit and significant association between certain areas of CSR and specific financial determinants. Ethical behavior, for example transparent lending policies, is positively correlated to enhanced profits and significantly associated with less NPL showing how ethical behavior helps foster trust and mitigate risk. Community donation projects have the highest correlation with new customers and market share, which ultimately leads to the establishment and acceptance of the branch. Most important, those that are connected to the banks social purpose particularly programs that help in teaching basic financial skills also show to be the best predictor with respect to greater profitability. This evidence shows we have the most direct business benefit from effort tied directly to the bank’s central mission. 67% of the changes in profit level of I branch are explained by a statistical model incorporating these CSR factors. This indicates that CSR is a proper strategy business investment for the branch. By instilling trust among local people, resulting in a stronger loan book, and attracting new customers, it boosts financial performance. It is noted in the research that the approach of branch leaders should be more aligned with the use of evidence-based techniques of CSR. These improvements cover everything from connecting CSR projects directly to financial objectives to enhancing communication with customers about CSR, as well as embedding the mission’s key functions such as financial education into everyday business operations. This report provides detail in addressing the localized, specific issues raised regarding CSR at the local level in African banking as well as insights to guide bank leaders of high corporate social responsibility (CSR) as it relates to community and business.
Undergraduate